Dinosaurs (Reptilia, Archosauria) at Museo de La Plata, Argentina: annotated catalogue of the type material and Antarctic specimens - Otero, Alejandro; Reguero, Marcelo Alfredo
A commented-illustrated catalogue of non-avian dinosaurs housed at Museo de La Plata, Argentina is presented. This represents the first commented catalogue of the La Plata Museum dinosaurs to be published. This includes the type material as well as Antarctic specimens. The arrangement of the material was made in a phylogenetic fashion, including systematic rank, type material, referred specimens, geographic and stratigraphic location, and comments/remarks, when necessary. A total of 13 type specimens of non-avian dinosaurs are housed at the collection of Museo de La Plata, including eight sauropods, one theropod, one ornithischian, and three ichnotaxa. There are four Antarctic specimens, one of which is a holotype, whereas other corresponds to the first sauropod dinosaur registered for that continent. Fil: Otero, Alejandro. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Reguero, Marcelo Alfredo. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina